Integration of Mechanical Load on Steam Expander - Bogeryd Andersson, William; Jacobs, Felix (My University, 2024)
This master’s thesis is performed in collaboration with Maston AB and Invencon AB. The thesis investigates, generates, and analyzes how mechanical load can be integrated on to a steam expander. Maston AB develops the steam expander and they are looking to widen the areas of usage of the product. This thesis explores the possibilities of connecting it to mechanical components and having the excess power go to a generator that is connected to the power grid. The steam expander originates from a neglected Saab project in the 1960s. When the project was put to bed, the engineer Ove Platell continued the development on his own with the company Ranotor AB. The development was after that continued by his son, Peter Platell who led the development until recent years. Today Stefan Larsson Mastonstråle of Maston AB recently joined forces to further develop the steam expander and have been making major progress. The study explores the integration of mechanical load, using a water pump and a generator as a case study, which is connected to the steam expander. The steam expander uses waste heat to run the pump and takes the waste power to a generator which is connected to the power grid. Our research suggests a concept that solves the issue of power distribution between the two components, in a way that minimizes waste. Potential drawbacks and limitations of the concepts are discussed and visualised. Alternative concepts are discussed as part of the research as well. The thesis proposes a final concept employing a power distribution system based on mechanical and electrical components, ensuring the water pump receives consistent speed and torque while the excess powers the generator. The system consists of several components, including a steam expander, generator, couplings, bevel gears, clutch, toroidal CVT, and ECU, designed to achieve efficient power distribution and control. The study’s objectives consist of concept generation, component comparison, market accessibility assessment, generator selection, load variation impact evaluation, and parameter role identification. Limitations include a focused scope, prototype constraint, material selection overview, limited economic analysis, and exclusion of human factors considerations. Ultimately, the thesis contributes to Maston AB and Ranotor’s goal of reducing industrial heat waste and advancing renewable energy generation. The proposed concepts and reviews are expected to benefit a broader area, where the pump can be switched out for other components. Also connecting the generator to other components rather than the power grid is an option.
Keywords: CVT; PMSG; Steam Expander; Steam Engine; ECU; Step-less gearing